Prognostic relevance of mucinous subtype in a population-based propensity score analysis of 40,083 rectal cancer patients - Tarantino, Ignazio; Hüttner, Felix; Warschkow, René; Schmied, Bruno; Diener, Markus K.; Ulrich, Alexis (Annals of surgical oncology, 2016)
The prognostic relevance of mucinous histology in colorectal cancer remains unclear, especially for rectal neoplasms. The objective of this study was to evaluate if mucinous subtype has a relevant impact on overall survival (OS) and cancer-specific survival (CSS) of patients with adenocarcinomas of the rectum.
Published online: 29 December 2015
Gesehen am 20.05.2020